2011
DOI: 10.1007/s10570-011-9605-0
|View full text |Cite
|
Sign up to set email alerts
|

Process variables that control natural fiber welding: time, temperature, and amount of ionic liquid

Abstract: A systematic study of variables that affect the fiber welding process is presented. Cotton cloth samples are treated with controlled amounts of 1-ethyl-3-methylimidazolium acetate for a series of times and temperatures. Diluting the ionic liquid with a volatile molecular co-solvent allows temporal and spatial control of the welding process not possible with neat ionic liquids. Materials are characterized by scanning electron microscopy, infrared spectroscopy, X-ray diffraction, and mechanical (tensile) testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 35 publications
1
60
0
Order By: Relevance
“…Upon IL removal, neighboring fibers re‐establish their hydrogen bond networks, delivering a fortified biocomposite which retains much of the polymer's native structure. Previous work in our lab demonstrated how careful control of NFW process variables (i.e., time, temperature, solvent) can significantly improve the tensile strength (in‐line and 45°) of nonwoven cotton cloth . We have also shown how NFW can improve the bulk mechanical strength of biopolymer yarns (i.e., cotton, linen, and bamboo) by more than 30% while incorporating activated carbons to fabricate high performance supercapacitor yarns for knittable textiles, or while integrating Pd‐based nanoparticle catalysts for wastewater treatment .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Upon IL removal, neighboring fibers re‐establish their hydrogen bond networks, delivering a fortified biocomposite which retains much of the polymer's native structure. Previous work in our lab demonstrated how careful control of NFW process variables (i.e., time, temperature, solvent) can significantly improve the tensile strength (in‐line and 45°) of nonwoven cotton cloth . We have also shown how NFW can improve the bulk mechanical strength of biopolymer yarns (i.e., cotton, linen, and bamboo) by more than 30% while incorporating activated carbons to fabricate high performance supercapacitor yarns for knittable textiles, or while integrating Pd‐based nanoparticle catalysts for wastewater treatment .…”
Section: Introductionmentioning
confidence: 68%
“…The SEM images in Figure show how NFW can change the morphology of yarn. Our early NFW studies focused on how these physical changes impacted material bulk mechanical properties (i.e., modulus, energy to break, etc.) after adjacent fibers mobilized and reformed during welding.…”
Section: Resultsmentioning
confidence: 99%
“…As all-cellulose composites based on nanocellulose are out of the scope of this thesis, they are not discussed here. Pathway 1 has gained more attention so far; it is based on partially dissolving the surfaces of either aligned cellulose fibers or fabrics, which leads to fibers being "glued" together during coagulation, as illustrated in Figure 3.5 (Soykeabkaew et al 2008;Gindl-Altmutter et al 2012;Haverhals et al 2012;Huber et al 2013;Dormanns et al 2016). Additionally, this approach can be utilised for short fiber "networks" such as isotropic pulp sheets (Gindl et al 2006;Piltonen et al 2016;Hildebrandt et al 2017;Sirviö et al 2017), filterpapers (Nishino & Arimoto 2007; a b…”
Section: All-cellulose Compositesmentioning
confidence: 99%
“…Afterwards, a systematic study of variables that affect the fiber welding process (IL quantity, temperature, time) was presented by Haverhals and co-workers. 182 It was shown that the quantity of IL introduced was the most influential parameter to control the amount and location of biopolymer modification. In addition to material reorganization, natural fiber welding opens biopolymers to possible chemical functionalization at…”
Section: Self-reinforced All-cellulose Composites (Accs)mentioning
confidence: 99%